UPAYA MENINGKATKAN KEMAMPUAN MOTORIK HALUS PESERTA DIDIK DENGAN AKTIVITAS BERMAIN (PLAYDOUGH) DI TK YAA BUNAYYA - Hikmawati Hikmawati; Takasun Takasun; Muhimatul Lailin (Jurnal Abdi Insani, 2022)
Children's physical development which includes gross and fine motoric affects the development of children in other aspects, namely independence and social emotional, cognitive, language, vision and hearing. Fine motor development of early childhood in Yaa Bunayya Kindergarten has not developed optimally. The purpose of this community service activity is to improve children's fine motor skills through playing activities using playdough at Yaa Bunayya Kindergarten, Blitar. This activity was held on November 17, 2021 with six participants. The methods of implementing the activities are: 1) The teacher invites the children to talk about the playdough material; 2) The teacher demonstrates how to mix playdough ingredients; The teacher gives an example of making ants from playdough; 3) The teacher asks the children to make ants from playdough. The assessment instrument for fine motor aspects uses performance. Children's achievements during play activities using playdough are: (1) Children are able to move their eyes and hands through playing activities using play dough; (2) Children are able to mix playdough ingredients; (3) Children are able to form neatly; (4) Children are able to show their work. Assessment rubrics are: BB (Not yet developed from all achievements); MB (Start growing from 1 achievement); BSH (Develops as expected from 2 to 3 achievements); BSB (Excellent progress from all achievements). The results of the assessment show that the average fine motor ability of children is 3.17 which is in the BSH criteria (Developing According to Expectations). The conclusion of this service activity is that efforts to develop fine motor skills of students with playdough activities at Yaa Bunayya Kindergarten still need to be done, with the hope that the criteria for fine motor skills of students can increase to the highest criteria, namely BSB (Excellent progress from all achievements).